Penguatan Kompetensi Pendidik Sanggar dalam Praktik Tata Rias Anak Usia Dini - Medilianasari, Renistiara; Rohmah, Naili; Sugiana, Sugiana (Universitas Pahlawan Tuanku Tambusai, 2025)
Serulingmas Dance Studio is one of the dance art studios located in Banjarnegara Regency, Central Java. In collaboration with Serulingmas Dance Studio, the community service team implemented a program to strengthen the competencies of studio educators through early childhood makeup training. This community service program involved studio educators who have the potential to facilitate the studio’s students. The aim of this program was to enhance the skills of the studio educators in early childhood makeup at Serulingmas Dance Studio. The implementation of the program consisted of several stages, including preparation, training, mentoring and evaluation, as well as monitoring. The results of the program had a highly positive impact on the partner. The studio educators were able to absorb the knowledge and information well, enabling them to apply early childhood makeup skills in the studio environment. The outcomes of the program were directly implemented in the Depo Pelita Traditional Creative Dance Festival.